Pengaruh Implementasi Media Pembelajaran Tas Ajaib Dalam Upaya Mengenal Identitas Diri Dan Keluarga Pada Siswa Kelas 1 SD Islam Al-Mubarok Surabaya - Al Fatich, Vahid Najich; Alamsyah, Artika Devi; Taqiardi, Khanza Hisyambara; Staniyah, Adduha Walidatus; Hendira, Galuh Shafwah Putri; Ramadhani, Tutitya Qodrianisa; Istiq'faroh, Nurul; Zahroh, Ulfi Aminatuz (CV. Kurnia Grup, 2024)
The present study aims to promote self-knowledge and familial awareness among children, thereby facilitating their socialization. The objective is threefold: first, to enhance students' interest and motivation in the learning process; second, to assist them in recognizing their own selves; third, to encourage interaction and collaboration among students; and fourth, to provide a learning experience that is both educational and enjoyable. Conventional learning media is often regarded as less appealing to early childhood students. This study proposes the utilization of